The physical basis of scoring athletic performance - Grammaticos, B. (New Studies in Athletics, 2007)
This article sets out to prove that it is possible to create scoring tables for the widest possible range of performance in athletic events. The author, a physicist who now works in the modeling of biological phenomena, describes a new scheme, based on a simple analytic expression. The scheme`s construction is based on two main ideas. The first is that the number of points attributed to a given performance should increase with the (useful) energy expenditure of the athletic effort. The second, inspired by the works of Dale Harder, is that the number of points should increase as the number of athletes who have realized a particular performance decreases. The two ideas converge with a proposal for a scoring system that closely approximates that currently used by the IAAF for the combined events except (by construction) for the lowest performances.